Overlooked or Ignored – Missing Elements in the Entrepreneurial Finance Policies: A Case of Introducing MUDRA Bank in India1. (23rd September 2016) - Sinha, Gaurav
Abstract : Sometimes the design of a policy is responsible for not achieving the desired results, and not really the implementation, which usually receives the blame.